Exploring Reading Strategies among English Education Students in Reading Academic Journal Articles - Anisah Almauizzah; Christianti Tri Hapsari (JET (Journal of English Teaching), 2026)
Reading academic journal articles often poses problems for EFL university students due to shopisticate language, unfamiliar vocabulary, and dense information. Therefore, the current study aims to explore the reading strategies utilized by English Education students when interacting with academic journal articles and to ascertain how these tactics help their comprehension. A total of 35 students from Universitas Negeri Semarang majoring in English Education Study Program participated in a descriptive qualitative study. The data was gathered by the SORS questionnaire and semi-structured interviews. Mean scores were calculated from questionnaire data, followed by thematic analysis used on interview data to achieve a greater insight into students' strategy utilization. The data demonstrated that students employed three categories of reading strategies: global reading strategies, problem solving strategies, support reading strategies. Overall, students’ strategy use fell into the moderate to high categories, with no strategies categorized as low. Within the three types of strategies, PROB were used most often (M= 3,95), indicating that students tend to focus on dealing directly with difficulties encountered during reading. Overall, the results indicate that English Education students actively utilize diverse reading strategies to support students in comprehending academic journal articles.